QUESTIONING THE SKULL: ZHUANGZI AND HAMLET ON DEATH - Peruzzi, Riccardo (Revista Dialectus - Revista de Filosofia, 2024)
This article aims to explore some aspects of our shared human experience of death through a parallel reading of Hamlet and Zhuangzi. These two classics belong to radically different cultural contexts, and both have traditionally been interpreted as texts in between philosophy and literature. As such, I hope this article will be of some interest for both students of world literature and transcultural philosophy, disciplines that, despite the contemporary academic distinctions, share much in common. Section 1 highlights some differences and similarities between Hamlet and Zhuangzi. Section 2 proceeds by elucidating three aspects of the problem of death approached by both texts (uncertainty; the death of others; my death). Section 3 examines two predominant perspectives in Chinese and European cultural backgrounds (the “individual” and the “cosmic” perspectives). Sections 4 analyzes how Hamlet approaches uncertainty, the death of others and my death from the individual perspective, while section 5 does the same for the cosmic perspective in Zhuangzi. In section 6, the two mirroring passages of the dialogues with the skull are compared, showing how the individual and the cosmic perspectives mutually implicate each other as two sides of the same coin.